2022
DOI: 10.3390/ijerph19159549
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Digital Cognitive–Behavioral Interventions in Supporting the Psychological Adjustment and Sleep Quality of Pregnant Women with Sub-Clinical Symptoms: A Systematic Review and Meta-Analysis

Abstract: The present meta-analysis investigated the overall and differential efficacy of digital cognitive–behavioral therapies (CBTs) vs. third-generation CBTs deployed to pregnant women in reducing sub-clinical depression, anxiety, and stress symptoms while fostering sleep quality and quality of life. A PRISMA-guided systematic search was used, including randomized controlled trials (RCTs) evaluating the above-mentioned interventions. Data were pooled using either the mean difference (MD) or standardized MD (SMD). Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…Our results were somewhat similar to the results of the previous meta-analysis conducted by Mancinelli et al specifically in depression-related outcomes (18). Regarding depression, by pooling PHQ-9 and EPDS together, they reported a significant effect for D.CBT in decreasing depressive symptoms after treatment, but there was no significant difference after six months of labor.…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were somewhat similar to the results of the previous meta-analysis conducted by Mancinelli et al specifically in depression-related outcomes (18). Regarding depression, by pooling PHQ-9 and EPDS together, they reported a significant effect for D.CBT in decreasing depressive symptoms after treatment, but there was no significant difference after six months of labor.…”
Section: F O R P U B L I C a T I O Nsupporting
confidence: 91%
“…The overall risk of bias was high in three studies (21,28,31), and low in two studies (18,29), and there were moderate concerns in the other nine studies (19, 20, 25-27, 30, 32-34). In terms of the randomization process, six studies reported an appropriate randomization approach with allocation concealment, therefore we classified them as low risk (26,27,29,(32)(33)(34), while it was determined that the other studies had some concerns.…”
Section: Quality Assessmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, greater flexibility in the structuring of interventions (ie, the number of sessions and time required to complete each session) is recommended, as it would support acceptability. These aspects might be particularly valuable, considering the high attrition rate of these interventions, which had already been pointed out by existing literature and was coherently reported by the included studies as well [66].…”
Section: Principal Findingssupporting
confidence: 53%
“…Future studies might benefit from including qualitative evaluations of the interventions' experience and overall usability, for instance, by foreseeing the use of semistructured interviews at the end of the intervention [64]. In this regard, it should be stressed that usability was not evaluated by any of the concluded research studies included in this review, although the criticality of adherence to interventions was highlighted as it emerged in previous studies [65,66]. Usability is conceptualized as the output of the interaction between the user and the tools (eg, website) used [67] and includes 5 main concepts [68]: ease of use, intended as learnability, experienced by users learning how to use a digital tool; the efficiency with which users interact with the digital tool; the memorability of how to use a digital tool to which the user has been already exposed; the errors users make, intended as the number of trials needed to make a certain action correctly; and the perceived users' satisfaction with the user experience.…”
Section: Principal Findingsmentioning
confidence: 99%